The capacity of banana trees to absorb radio frequency waves / Nor Hidayah Daud - Daud, Nor Hidayah
This paper presents the case study about the capability of banana tree to absorb radio frequency (RF) waves. The results were classified into three particular types of medium propagations such as fruits, leaves and trunks. This research was conducted using spectrum analyzer and a simple set-up on the Yagi-Uda antenna. The distances and height of banana tree from the transmitting antenna arc taking into consideration in this data collection techniques. Comprehensive results were performed to find the relationship between the line-of-sight (LOS), antenna (Yagi-Uda), power radiation and also the distance between the transmitter and receiver that will affect the signal strength reception. From the results obtained, it shows that fruits have more capability to absorb RF waves followed by the leaves and trunk.